2020
DOI: 10.1111/dth.14488
|View full text |Cite
|
Sign up to set email alerts
|

Fractional carbon dioxide laser‐assisted delivery of lyophilized‐growth factors is a promising treatment modality of post‐acne scars

Abstract: Lyophilized-growth factors (L-GFs), is a new platelet rich plasma (PRP) preparation that is standardized in growth factors concentrations. The aim of this study was to compare the therapeutic efficacy of ablative fractional CO 2 laser in combination with L-GFs vs PRP in post-acne scars. This study was conducted on 45 patients presented with facial post-acne scars. Each patient received three sessions of fractional CO 2 laser on both sides of the face followed by topical application of L-GFs on one side and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…A recent study by Neinaa et al. [ 17 ] reported significant clinical improvement of post-acne scars treated with AFCL combined with PRP, as evidenced by the significant reduction in both the Clinique des Cicatrices d’Acné and Goodman and Baron’s qualitative scar scale scores with minimal adverse effects. In that study, they found that AFCL-assisted delivery of lyophilized growth factors, a new PRP preparation that is standardized in growth factor concentrations, reached a higher degree of clinical improvement and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Neinaa et al. [ 17 ] reported significant clinical improvement of post-acne scars treated with AFCL combined with PRP, as evidenced by the significant reduction in both the Clinique des Cicatrices d’Acné and Goodman and Baron’s qualitative scar scale scores with minimal adverse effects. In that study, they found that AFCL-assisted delivery of lyophilized growth factors, a new PRP preparation that is standardized in growth factor concentrations, reached a higher degree of clinical improvement and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 18 , 19 Several studies suggested that fractional CO 2 laser treatment combined with PRP could reduce edema and prolonged erythema after laser treatment. 20–22 The majority of studies available demonstrated that using PRP in combination with CO 2 for the management of atrophic acne scars could be superior to topical intradermal PRP alone. 23 , 24 Consistent with such findings, our study showed that with the application of PLT, the erythema and edema associated with CO 2 laser treatment were able to resolve completely within 2 days.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, recent studies showed a superiority of efficacy when this procedure is associated with platelet rich plasma (PRP) or Lyophilized-growth factors (L-GFs). 29,30 Regarding photorejuvenation and resurfacing, a recent systemic review of 1093 patients has demonstrated the effectiveness of ablative lasers in several indications, highlighting their superiority if compared to nonablative lasers in the field of resurfacing.…”
Section: Resurfacingmentioning
confidence: 99%
“…A recent meta‐analysis by Zhang et al has shown that although fractional CO 2 laser is a good option for the treatment of acne scars, in reality its effectiveness appears to be equal to nonlaser CO 2 therapies (eg, nonfractional laser treatments, fat grafting, chemical stripping preparation). Conversely, recent studies showed a superiority of efficacy when this procedure is associated with platelet rich plasma (PRP) or Lyophilized‐growth factors (L‐GFs) 29,30 …”
Section: Indications Of Laser Co2mentioning
confidence: 99%
See 1 more Smart Citation